Robust trioptical-state electrochromic energy storage device enabled by reversible metal electrodeposition - Eh, Alice Lee-Sie (2022)
Reversible electrochemical mirror (REM) electrochromic devices based on reversible metal electrodeposition are exciting alternatives compared with conventional electrochromic because they offer electrochemical tunability in multiple optical states, long durability, and high contrast. Different from conventional electrochromic materials, of which the color change depends on the intercalation/deintercalation of ions into electrochromic films, the change in the optical states of REMs is based on the reversible electrodeposition and dissolution of metal. In this study, a REM electrochromic device with a Cu hybrid electrolyte composed of aqueous and nonaqueous components is proposed, which serves as an electrolyte reservoir that hosts Cu ions for reversible electrodeposition/dissolution. The hybrid electrolyte promotes the electrochemical reversibility of the Cu redox, an enhanced electrochromic performance, and a robust cycling stability of 5000 cycles (minor degradation of 4.71%). The investigation of the discharging/charging of the Cu hybrid REM device reveals that the Cl-/ClO- redox mechanism occurs at the cathode. Finally, an unprecedented dual-functional Cu hybrid REM energy storage device has been realized.